Application of Rapid Rehabilitation Surgical Nursing Combined With Continuous Nursing in Self-Care Ability, Medication Compliance and Quality of Life of Renal Transplant Patients - Song, Linyan; Jin, Qing; Zhu, Liying; Liu, Zhe; Cheng, Wenjuan (Frontiers in Surgery, 2022)
【Abstract】Objective：To explore the effects of rapid rehabilitation surgery (FTS) nursing combined with continuous nursing on self-care ability, medication compliance and quality of life of patients after renal transplantation. Methods:A total of 60 patients who underwent kidney transplantation in our hospital from January 2019 to January 2021 were selected and randomly divided into a control group and an observation group according to a random number table, with 30 cases in each group. Collect two general data for comparison. Record clinical indicators and evaluate the self-care ability, medication compliance, and quality of life of the two groups of patients. During the follow-up, the admissions of patients with complications were recorded. Results:There were no significant differences in general information such as gender, age, BMI, educational level, marriage relationship, and dialysis method between the two groups. There was no significant difference in the time of first intake, blood glucose, creatinine, urea nitrogen, blood potassium or postoperative hospital stay between the two groups. There was no significant difference in the postoperative physical, mental, psychological, social and environmental dimensions and overall comfort between the two groups. The scores of cognitive symptom management, exercise and communication with doctors in the two groups in post-intervention were higher than those in pre-intervention, and the scores in the observation group in post-intervention were higher than those in the control group. Medication compliance in the observation group was higher than that in the control group. In pre-intervention, the differences in scores of physical health, psychology/spirit, society/economy, family and other dimensions of quality of life between the two groups were not statistically significant. In post-intervention, the scores of quality of life of the observation group were higher than those of the control group. The admission rate of complications in the observation group was lower than that in the control group. Conclusion: FTS nursing can help patients with renal transplantation to obtain more stable postoperative blood pressure, renal function and other indicators and comfort. On this basis, combined with continuous nursing can improve patients' self-care ability and medication compliance, which is of great significance to improve the quality of life of patients.